Perkembangan Gerakan Earth Hour sebagai Bentuk Pencegahan Perubahan Iklim Dunia Tahun 2007-2015 - Rohy, Wolter Kinsky (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis research aims to analyze the development of the Earth Hour, which started in 2007, in Sidney, Australia. The Earth Hour, initiated by WWF, is a movement that works by encouraging people to turn off the light for an hour in the last week of March. Other than that, the Earth Hour has also managed to initiate other solutions for various climate change issues. This research look into the Earth Hour movement based on the standpoint of the recipient and the messenger. The recipient standpoint is being analyzed through the Convergence Theory, where the focus is the people, who joins the organizations based on their similarities in vision and mission statements and how they influence the national policy, from six sample countries. The messenger is WWF that works through the five strategies of mobilizing the global civil society, which are as follows, networking, lobbying, visibility, framing, and swarming.Keywords: strategy, convergence theory, earth hour movementDOI : https://doi.org/10.33005/jgp.v4i01.1930